Superfícies de ângulo constante: sua relação com cristais líquidos e classificação em R 3 , S 2 × R e I ×f E 2 - Cevolani, Renata Pilon (2019)
We say that a surface is a constant angle surface when its unit normal vectors field form a constant angle whith a prefixed direction field of the space. Such surfaces have aroused great interest by reasearchers of diffe rential geometry. The motivation came mainly from [4], which is chronolo gically the first work related to this theme. There, the authors analyzed the case of constant angle surfaces in R3, also showing its relations with liquid crystals. After that, several authors have been dedicated to the study of these surfaces, considering other spaces and other particular cases. In this work, following what was done in [4], [8] and [10], we studyed and classify the constant angle surfaces in the spaces R3, S2 R and in the warped product I x f E2, where f is any strictly positive function.